Spelling Bees for Improving Students' Pronunciation Skills - Huda, Nurul; Hidayati; Edi; Hudri, M; Ilham; Olatunji, Olusola (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Correct pronunciation is a crucial aspect of learning English that is often challenging for many students. Traditional methods of teaching pronunciation usually need to be more interesting and exciting for students, so a more innovative and interactive approach is required. This research aims to determine the effectiveness of the Spelling Bee in improving students' speaking pronunciation. This quantitative method uses quasi-experimental research applied to ninth-grade junior high school students. This research uses an experimental group and a control group. The experimental group consisted of 22 students of 10 men and 12 women, while the control group consisted of 22 students of 13 men and 9 women. In collecting data, pretest and posttest were used to determine the improvement in students' speaking pronunciation. The data analysis technique uses inferential statistical analysis. The research results show that the Spelling Bee can be an effective strategy in helping EFL students improve their pronunciation skills. This research implies that research contributes to improving the quality of English language teaching and learning and the development of professionalism of teaching staff in the language field.